The complex cultural property’s protection project of the Italian police (Academic Journal of Internal Affairs, 2019)
In Italy operates one of the most complex systems for defence of cultural assets. The aim of this study is to see into the art object defence of the Italian Gendarmerie and finance authority and to make mechanism and process of their operation easier to understand. The Italian authorities for art object defence gained professionalism by education, sincerity and professional knowledge. Beside elaboration of the publications are further bases of this article observations during study tours and interviews made in the period spent at Italian authorities.
Keywords: cultural property’s protection; police; Italy